2016
DOI: 10.1590/1677-5449.004616
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da termoablação da veia safena magna na coxa, com e sem tumescência

Abstract: Background: Endovenous laser treatment of saphenous veins offers patients a procedure with low rates of complications and an early return to occupational activities. Objective: To compare rates of formation of bruising, of paresthesia along the path of the great saphenous vein (GSV), and of GSV obliteration 30 days after thermal ablation in the thigh, performed with or without tumescence and using two different types of fiber. Methods: This was a prospective study, analyzing three groups of patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…A number of explanations have been proposed for the relationship between tumescence and lower rates of paresthesia. 10 However, this variable could not be evaluated in the present study because the technique was used infrequently (23.3%). Erzinger et al 10 made this comparison and found that 7 days after surgery, paresthesia was significantly less frequent among patients in whom the tumescence technique had been used.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…A number of explanations have been proposed for the relationship between tumescence and lower rates of paresthesia. 10 However, this variable could not be evaluated in the present study because the technique was used infrequently (23.3%). Erzinger et al 10 made this comparison and found that 7 days after surgery, paresthesia was significantly less frequent among patients in whom the tumescence technique had been used.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, there was a high prevalence of complaints of local “dormancy”, which was higher than rates reported in previous studies. 10 , 24 , 28 This may have occurred for a number of reasons: use of ablation in distal segments, not employing tumescence, exeresis of varicose collaterals during the same session, administration of conventional sclerotherapy and/or sclerotherapy with dense foam, and even because there was a specific question on the postoperative control protocol. On the other hand, it was impossible to estimate the duration of this symptom, because the question was only posed once, at the 7-day follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations